Exploring the Nexus Between Macroeconomic Indicators and Stock Market Performance in Indonesia: A Dual Index Approach - lailatus saadah laila; Rihlati Hajjah (Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the influence of macroeconomic variables—namely inflation, interest rate (BI Rate), and the rupiah exchange rate—on the LQ45 Index and the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange during the period 2019–2023. The approach used is quantitative associative with monthly time series data comprising 60 samples, obtained from the official websites of Bank Indonesia, the Indonesia Stock Exchange (IDX), and Yahoo Finance. The analytical method employed is multiple linear regression. The results show that, partially, inflation and the rupiah exchange rate have a significant effect on both the LQ45 and JII indices, while the interest rate does not have a significant effect on either index. Simultaneously, all three independent variables significantly influence both stock indices. The coefficient of determination (Adjusted R²) for the LQ45 index is 0.429 and for the JII is 0.547, indicating that inflation, interest rates, and exchange rates contribute significantly to the fluctuations of these stock indices. These findings offer important implications for investors and capital market participants in considering macroeconomic factors before making investment decisions in either the conventional or sharia stock markets.